Семен Виноградов - Краснова Вера Владимировна (Удмуртия, 2014)
Экземпляры: 5 (20160701) / Инвентарный номер: 48735 / Цена: 108.00 / Сис.шифр: 85.143(Удм) / Авт.знак: В 49 / ГРНТИ: 18.31.31 / ББК: 85.143(Удм)